Increased Conformity to Social Hierarchy Under Public Eyes - Kim, Daeeun; Kim, JuYoung; Kim, Hackjin (Frontiers in Psychology, 2021)
Why would people conform more to others with higher social position? People may place higher confidence in the opinions of those who rank higher in the social hierarchy or they may wish to make better impressions on people of higher social status. We investigated how individual preferences for novel stimuli are influenced by the preferences of others in the social hierarchy and whether anonymity affects such preference changes. After a manipulation of their social rank, participants were asked to indicate how much they liked or disliked a series of images. They were then shown the rating given to each image by a partner (either inferior or superior in social rank) and were given a chance to adjust their ratings. The participants were more likely to change their preferences to match those of a superior partner in the public vs. private condition. The tendency to conform to the superior partner’s views was stronger among those with a higher social dominance orientation and among those with greater fear of negative evaluation by others. Altogether, the findings suggest that motivation to make better impressions on people of higher social status can be the major driver of conformity to others with higher social position.